Pengaruh Kepemimpinan Kepala Sekolah dan Kompensasi Terhadap Motivasi Kerja Guru - Imam Muhtadin (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2022)
The purpose of the study was to find out the influence of the principal's leadership and compensation on work motivation. This research uses competency test methods and path analysis data. The sample selection was taken from a population of 144 private vocational school teachers in South Tangerang City. The data can be obtained from the results of the distribution of questionnaires to 106 respondents by giving a score on each answer according to the Likert Scale. Research results: Principal leadership (X) affects work motivation (Y1) with a path coefficient of 0.411; Compensation (X2) affects work motivation (Y1) with a path coefficient of 0.449.